The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13122781
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Operator Centered Outcomes in Implant Dentistry: Comparison between Fully Digital and Conventional Workflow for Single Crown and Three-Unit Fixed-Bridge

Abstract: Background: Scientific information about the effects of implant therapy following a precise workflow and patient and operators’ preferences should be considered to choose which implant treatment protocol to use, and to achieve patient’s satisfaction and functional results. The aim of this study was to analyze implant rehabilitations with a fully digital workflow and compare this approach with a conventional one. Methods: This study comprises 64 patients treated with a fully digital approach and 58 patients tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…The rapid evolution of CAD/CAM (Computer-Aided Design/Computer-Aided Manufacturing), and the advancements of its application to dentistry have heralded a series of innovations in all branches, especially in implantology and restorative dentistry, where its association with new materials presents the clinician a new treatment possibility that is both economically advantageous and clinically resilient [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid evolution of CAD/CAM (Computer-Aided Design/Computer-Aided Manufacturing), and the advancements of its application to dentistry have heralded a series of innovations in all branches, especially in implantology and restorative dentistry, where its association with new materials presents the clinician a new treatment possibility that is both economically advantageous and clinically resilient [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of digital workflow in oral and maxillofacial surgery is expanding in the areas of performing osteotomies, zygomatic implants, bone regeneration, orthognathic surgeries where greater surgical precision and accuracy is essential [ 4 ]. To satisfy the high expectations of patients and to ensure an adequate and predictable long-term outcome, implant treatment requires prosthodontically guided, three-dimensional assessment and planning [ 5 ]. DWF can optimize the process, as they provide valuable diagnostic information and facilitate backward planning to improve safety and efficiency, which contribute to a more predictable outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal positioning ensures adequate bone volume surrounding the implant with correct load distribution. Whilst freehand (FH) implant placement has been the standard approach [ 5 , 6 ], the surgical accuracy of this method can be limited. Despite the use of anatomical landmarks or stents, FH surgery relies on good three-dimensional (3D) spatial awareness and high levels of surgical experience to place the dental implant correctly within the limited volume of residual bone [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 14 selected studies, 6 studies showed data on guided and non‐guided implant surgery (Arısan et al, 2010; Fortin et al, 2006; Nkenke et al, 2007; Pozzi et al, 2014; Vercruyssen et al, 2014; Youk et al, 2014), 7 studies reported on implant impressions (De Angelis et al, 2020; Delize et al, 2019; Guo et al, 2019; Joda & Bragger, 2016; Mangano & Veronesi, 2018; Schepke et al, 2015; Wismeijer et al, 2014) and 3 studies compared conventional and digital fabrication of veneered and monolithic restorations (Delize et al, 2019; Joda, Ferrari, et al, 2018; Mangano & Veronesi, 2018). In two studies, outcomes of both impressions and final restorations were evaluated (Delize et al, 2019; Mangano & Veronesi, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the same clinicians followed strictly all surgical and prosthetic steps and an external assistant performed all evaluations directly after the impression procedure to avoid the possibility of the procedure effect being erased from the patient's memory. However, the results of this study have to be interpreted with caution, due to the retrospective nature of the study and the small and strictly selected sample (De Angelis et al, 2020). Joda et al also used the VAS scale to evaluate patient's opinion on optical impressions compared with conventional ones.…”
Section: Discussionmentioning
confidence: 99%